2008
DOI: 10.1021/om800408w
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Disproportionation of Carbon Dioxide at an Iron(II) Center

Abstract: The reaction of cis-Fe(dmpe) 2 H 2 (1) with 13 C-labeled carbon dioxide (CO 2 ) was inVestigated, and trans-[Fe(dmpe) 2 (CO)H] • [HCO 3 ] (5) was identified as a reaction byproduct. Both the carbonyl ligand and the bicarbonate anion are deriVed from CO 2 , and this effectiVely constitutes a disproportionation of CO 2 to CO and CO 3 2-. trans-[Fe(dmpe) 2 (CO)H].[HCO 3 ] (5) was characterized by crystallography and by NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…The related C 3 v P 3 E iron hydride complexes (E = B, N, Si) exhibit 10‐ to 100‐fold faster reaction rates compared to our case. Finally, Field reported octahedral cis ‐Fe(dmpe) 2 H 2 (dmpe= Me 2 PCH 2 CH 2 PMe 2 ) for which the reaction with CO 2 is complete within 1 min , . Notably, the complexes with ligands with stronger trans effect afford larger rate constants.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The related C 3 v P 3 E iron hydride complexes (E = B, N, Si) exhibit 10‐ to 100‐fold faster reaction rates compared to our case. Finally, Field reported octahedral cis ‐Fe(dmpe) 2 H 2 (dmpe= Me 2 PCH 2 CH 2 PMe 2 ) for which the reaction with CO 2 is complete within 1 min , . Notably, the complexes with ligands with stronger trans effect afford larger rate constants.…”
Section: Resultsmentioning
confidence: 97%
“…Although tempting to draw conclusions on mechanism as either inner or outer sphere from this literature comparison, this analysis is arguably complicated by the relative bond dissociation free energies for the differing M–H species. We sought then to compare our values to those for reported iron hydride species , . To our knowledge, no such kinetic study has been reported for an iron hydride complex.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Allen et al have recently isolated an iron carbonyl complex with a bicarbonate counterion (Fe(dmpe) 2 (CO)H)(HCO 3 ) with dmpe = 1,2 bis(dimethylphosphino)ethane, resulting from the iron(II) -mediated reductive disproportionation of CO 2 [104] , although the reaction mechanism is still speculative. In a related system, Karsh et al [9] had observed, during the reaction of CO 2 with Fe(PMe 3 ) 4 , the formation of a side -on complex Fe(CO 2 )(PMe 3 ) 4 and of a carbonyl carbonate species Fe(PMe 3 ) 3 (CO)(CO 3 ).…”
Section: Reduction Reactionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In contrast to other CO 2 reduction processes that produce CO as feedstock, [12,13] reductive disproportionation is unique in that CO 2 itself serves as the ultimate oxygen atom acceptor en route to the production of inorganic carbonate. [1][2][3][4][5][6][7][8][9][10][11] In contrast to other CO 2 reduction processes that produce CO as feedstock, [12,13] reductive disproportionation is unique in that CO 2 itself serves as the ultimate oxygen atom acceptor en route to the production of inorganic carbonate.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In contrast to other CO 2 reduction processes that produce CO as feedstock, [12,13] reductive disproportionation is unique in that CO 2 itself serves as the ultimate oxygen atom acceptor en route to the production of inorganic carbonate. [2][3][4][7][8][9][10][11] Of these complexes,h ighly reduced Group 6a nd 8m etal carbonyl dianions have been established as the most operationally simple CO 2 reductive disproportionation archetypes as they produce discrete alkali or alkaline-earth metal carbonates and av olatile,n eutral transition-metal carbonyl complex upon addition of two equivalents of CO 2 . [2][3][4][7][8][9][10][11] Of these complexes,h ighly reduced Group 6a nd 8m etal carbonyl dianions have been established as the most operationally simple CO 2 reductive disproportionation archetypes as they produce discrete alkali or alkaline-earth metal carbonates and av olatile,n eutral transition-metal carbonyl complex upon addition of two equivalents of CO 2 .…”
mentioning
confidence: 99%